Combined construction of injectable tissue-engineered bone with CPC and BMMSCs and its study of repair effect on rabbit bone defect model - Li, Guangjun (J Musculoskelet Neuronal Interact, 2020)
OBJECTIVE: to investigate the combined construction of injectable tissue-engineered bone with calcium phosphate bone cement composite (CPC) and bone marrow mesenchymal stem cells (BMMSCs). METHODS: The proliferation activity of BMMSCs encapsulated was detected by CCK8 method on the 7(th) day after its self-coagulation by CPC. qRT-PCR was used to detect the expressions of mRNA. The microcapsules of BMMSCs combined with CPC were completely filled in the defect site in the experimental group, and the control group not filled. The two groups were sutured and routinely reared, double upper limb X-ray examination performed after operation. RESULTS: Those of two groups were on the rise over time, which were higher at the 1(st), 3(rd), 5(th) and 7(th) days than those at the previous time points (all P<0.05). The relative expressions of ALP and CALCR at the 7(th) day were higher than those at the day in BMMSCs combined with the CPC group and BMMSCs group (all P<0.05). The relative expression of CALCR was significantly higher in BMMSCs combined with the CPC group than that in the BMMSCs group on the 7(th) day (P<0.05). CONCLUSION: With good cell activity and biological activity, the combined construction of the tissue-engineered bone with BMMSCs and CPC can be used as an ideal treatment material for bone tissue repair and connection.